A Study of Interpretation of Mantoux Test in Pediatrics age Group (5-18 Years of Age) (Indian Journal of Public Health Research & Development, 2021)
Objective: To establish the role of Mantoux test in diagnosis of tuberculosis in children.Methods: The age group selected for this study was 5-18 years and period of study was Aug 2018 to Feb 2020.Children attending to our OPD with the c/o fever & weight loss for > 2 months were advised to undergo Mantoux test along with CBC & ESR , CHEST X-RAY & Sputum Examination for AFB after taking detailed history including contact history of tuberculosis & clinical examination .Result: Out of 100 cases 64 (64%) were to be found to be suffering from tuberculosis disease. Rest 36(36%) were improved with symptomatic treatment and antibiotic treatment.According to age these children were divided into two group i.e,5-10 years and 10-18 years. It showed association between Mantoux test and tuberculosis was more in age group between 5-10 years in comparison to age group between 10- 18 years .Conclusion: Childhood tuberculosis is an indirect index of the prevalence of tuberculosis in the community. Clinical presentation may be atypical and leads to delay in diagnosis. Children can present with TB at any age, but the majority of cases present with TB at any age, but the majority of cases present between 1 and 4 years. Disease usually develops within 1 year of infection- the younger, the earlier and the more disseminated. A positive tuberculin test does not indicate the presence or extent of tuberculosis; it only indicates infection. Mantoux has to be interpreted carefully. A careful history, complete physical exam, and focused laboratory evaluation are essential for determining the cause and initiating treatment. Occasionally A positive Mantoux test may be the only evidence of disease.
Keywords: TU(Tuberculin Unit), TB(Tuberculosis), ATT(Anti Tubercular Treatment), Mx(Mantoux), AFB (Acid Fast Bacilli)